1997
DOI: 10.1046/j.1365-2133.1997.d01-1237.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endothelial nitric oxide synthase in human eccrine clear cells

Abstract: Nitric oxide is generated from L-arginine by nitric oxide synthase (NOS), which has at least three isoforms; endothelial-type NOS (eNOS) and brain-type NOS (bNOS) are constitutive enzymes, and inducible-type NOS (iNOS) is expressed after stimulation. Studies by the avidin-biotin immunocomplex method, revealed eNOS immunoreactivity exclusively in the human eccrine clear cells. No eNOS immunoreactivity was observed in the eccrine dark cells or myoepithelial cells. No staining of iNOS or bNOS was observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…28,29 We found iNOS and NT reactivity in eccrine glands both in leprosy lesions and in control skin, which indicate that iNOS and NT expression is not specific for leprosy. Eccrine glands have previously been shown to be positive for neuronal nitric oxide synthase (nNOS) 30 and endothelial nitric oxide synthase (eNOS), 31 depending on the method of fixation. Interestingly, in an AFB-positive nerve biopsy from a BT/RR patient we found strong NT reactivity in the macrophages and fusiform cells surrounding and infiltrating the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 We found iNOS and NT reactivity in eccrine glands both in leprosy lesions and in control skin, which indicate that iNOS and NT expression is not specific for leprosy. Eccrine glands have previously been shown to be positive for neuronal nitric oxide synthase (nNOS) 30 and endothelial nitric oxide synthase (eNOS), 31 depending on the method of fixation. Interestingly, in an AFB-positive nerve biopsy from a BT/RR patient we found strong NT reactivity in the macrophages and fusiform cells surrounding and infiltrating the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…eNOS is present in the sweat glands. Interestingly, eNOS-immunoreactive cells coincided with clear cells in the eccrine secretory gland (57). NO is associated with Cav-activated K+ channels in various cell types such as human dermal papilla cells (58), bovine aortic smooth muscle cells (59), porcine coronary artery smooth muscle cells (60), rabbit cerebral artery smooth muscle cells (61) and guinea pig vascular and tracheal smooth muscle cells (62).…”
Section: Discussionmentioning
confidence: 99%
“…Since COX-derived prostanoids can increase cAMP (O'Keefe et al 1992;Smyth et al 2009), it is plausible that COX may contribute to the β-adrenergic sweating. In addition, NOS in sweat glands (Shimizu et al 1997) may be stimulated by β-adrenergic receptor activation, as observed in the above-mentioned studies using human conduit artery (Cardillo et al 1997;Casey et al 2011), and this ultimately would induce an increase in cGMP. However, an earlier study reported that elevations in cGMP did not directly increase sweat rate in eccrine sweat glands of the monkey palm under in vitro conditions (Sato & Sato, 1984a).…”
Section: Introductionmentioning
confidence: 88%